Transcarceration: notes on a psychoanalytically-informed theory of social practice in the criminal justice and mental health systems - Arrigo, Bruce A. (Crime, law and social change, 1997)
The application of Lacanian psychoanalytic semiotics to the intersecting categories of criminal justice and mental health is relatively novel. In this paper the phenomenon of transcarceration or the repeated channeling of disordered defendants (subjects) through institutional regimes of discipline and coercion is outlined. Attention is directed at the intra-psychic and intersubjective mechanisms responsible for the structuring of discourse. Lacan's schematization on the constitution of master narratives through the Discourse of the Master is also delineated. The author concludes by demonstrating how transcarceration is fundamentally about language and privileged speech patterns which agents of both systems as well as subjects themselves perpetuate.